The novel concepts and practices of firm innovativeness: the mediating and moderating impacts - Abang Azlan, Mohamad; T., Ramayah; Lo, May-Chiun (Inderscience Enterprises Ltd., 2016)
The objective of this study is to propose a conceptual model that blends the dimensions of knowledge management, information technology capability, innovative culture and firm innovativeness into a single framework for practitioners and academicians. In conceptualising the model, this study reviewed a range of existing literature. The findings identified: 1) four processes of knowledge management that represents the construct; 2) information technology capability as a variable that mediates the relationship between knowledge management and firm innovativeness; 3) innovative culture as a variable that moderates the link between knowledge management and information technology capability. The resulting conceptualisation is meant for evaluating the potential strategic model for firms to implement information technology capability and innovative culture. It is posited that the proposed conceptual model, when implemented, would enable practitioners a better understanding on factors that enhance firm innovativeness.